MODERASI BERAGAMA SEBAGAI PILAR PENDIDIKAN ISLAM DALAM MASYARAKAT MULTIKULTURAL - Wahab Subagja, Robie; Abdurrohim; Siti Khulasoh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article explores the concept of religious moderation as a fundamental principle in Islamic education within multicultural societies. As religious extremism and intolerance pose serious threats to social harmony, religious moderation emerges as an educational approach that promotes tolerance, justice, and balance (tawassuth, tasamuh, tawazun, and i'tidal). Through a literature review method, the study analyzes scholarly discussions, Islamic perspectives, and the role of educational institutions in instilling values of moderation. The findings show that religious moderation aligns with core Islamic teachings and is essential for building a peaceful society rooted in mutual respect and pluralism. Keywords: Religious moderation, Islamic education, multicultural society, tolerance, tawassuth